Modelo de apoio à aprendizagem de gestão de cadeia de suprimentos utilizando a metodologia system dynamics - Lopes, Luís Sérgio Paçó (Universidade Federal de São Carlos, 2009)
In the 80 s, a new competitive managerial approach, named Supply Chain Management (SCM), has begun an innovative behavior in the operation area. The advances of logistics, information technology, and organizational studies made up conditions for the organizations to operate according to this vision which, besides new opportunities, also created a series of questions to be answered. The organizations started being managed under a wider perspective and their operations contemplated a bigger integration among clients and suppliers. Therefore, additional knowledges were necessary if such new perspective of management would be used. Supply Chain (SC) managers need support from new ways of organizational learning to deep the understanding of SC operation and, this way, to receive helps for strategy formulations and decision making. This work intends to build a theoretical model and simulation of SCM. Experiment of simulation model betters the option for new strategies through managerial learning on effective performance of a SC. New strategies are defined with the cause-effect relationship to shape a SC structure and actions which take the strategic alignment of belonging organizations. A coordinated application of such actions betters the competitiveness, in a sustainable way, to the enterprises as well their chains.
Keywords: Gestão de suprimentos; Logística; Simulação; System Dynamics; ENGENHARIAS::ENGENHARIA DE PRODUCAO